2020
DOI: 10.15210/rbes.v8i1.18315
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and morphological characteristics of quinoa grown in the southern region of Rio Grande do Sul State

Abstract: The objective of the present study was to describe the morphological characteristics that allow the differentiation of cultivars and to evaluate the agronomic characteristics that can determine the yield of Chenopodium quinoa cultivated in the southern part of Rio Grande do Sul. Quinoa is a pseudocereal that it is originally from the Andes region; it is consumed throughout the world due to its nutritional characteristics. Its introduction and production in Brazil are recent, so studies that make possible the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
2
2
0
3
Order By: Relevance
“…In addition, these traits were highly variable associated with variables. This behavior was also observed in quinoa materials evaluated in the Rio Grande do Sul region of Brazil (Vergara et al 2020) and in cultivars of Quinoa Blanca de Jericó, expressed in different pigmentations within individuals in structures such as panicles and stems. These variations allow plants to adapt more quickly to environmental conditions (Alandia et al 2020).…”
Section: Resultssupporting
confidence: 55%
“…In addition, these traits were highly variable associated with variables. This behavior was also observed in quinoa materials evaluated in the Rio Grande do Sul region of Brazil (Vergara et al 2020) and in cultivars of Quinoa Blanca de Jericó, expressed in different pigmentations within individuals in structures such as panicles and stems. These variations allow plants to adapt more quickly to environmental conditions (Alandia et al 2020).…”
Section: Resultssupporting
confidence: 55%
“…In addition, these traits were highly variable within the same accessions, that is, there was high heterogeneity in the characteristics associated with these variables. This behavior was also observed in quinoa materials evaluated in the Rio Grande do Sul region of Brazil [ 21 ] and in cultivars of Quinua Blanca de Jericó, expressed in different pigmentations within individuals in structures such as panicles and stems. These variations allow plants to adapt more quickly to environmental conditions [ 22 ].…”
Section: Discussionsupporting
confidence: 57%
“…Studies also show a strong correlation between panicle diameter and yield (Hussain et al, 2020); the diameters in this study were between 8 and 39 cm, results similar to those found by Manjarres et al (2021b), where a high diversity is reported at the interindividual level, mainly in the length, diameter, and color of the panicle. Manjarres et al (2021a) reported that although qualitative variables constitute a fundamental tool to determine the adaptation strategies of plants and are used as varietal descriptors (Katwal and Bazile, 2020), in their study these traits presented a wide genetic variability, as shown shows in the different colorations of the striae, axils, panicles and seeds This behavior was also observed in quinoa materials evaluated in the Rio Grande do Sul region of Brazil (Vergara et al, 2020) and in cultivars of Quinoa Blanca de Jericó, expressed in different pigmentations within individuals in structures such as panicles and stems.…”
Section: Discussionmentioning
confidence: 91%